High Level of Nitrogen Makes Tomato Plants Releasing Less Volatiles and Attracting More Bemisia tabaci (Hemiptera: Aleyrodidae) - Islam, Md. Nazrul; Hasanuzzaman, Abu Tayeb Mohammad; Zhang, Zhan-Feng; Zhang, Yi; Liu, Tong-Xian (Frontiers in Plant Science, 2017)
Tomato (Solanum lycopersicum) production is seriously hampered by the infestation of the sweetpotato whitefly, Bemisia tabaci MEAM 1 (Middle East-Asia Minor 1). The infestation behavior of the whiteflies could be affected by the quantity of plant released volatile organic compounds (VOCs) related to nitrogen concentrations of the plant. In this study, we determined the infestation behavior of B. tabaci to the tomato plants that produced different levels of VOCs after application of different levels of nitrogen with a wind tunnel and an olfactometer. We also analyzed the VOCs released from nitrogen-treated tomato plants using solid phase microextraction and gas chromatography-mass spectrometry. The results revealed that the production of eight VOCs (β-pinene, (+)-4-carene, α-terpinene, p-cymene, β-phellandrene, α-copaene, β-caryophyllene, and α-humulene) was reduced after the plants were treated with high levels of nitrogen. However, more whiteflies were attracted to the tomato plants treated with high levels of nitrogen than to the plants treated with normal or below normal levels of nitrogen. These results clearly indicated that nitrogen can change the quality and quantity of tomato plant volatile chemicals, which play important roles in B. tabaci host plant selection.